2011
DOI: 10.5194/acp-11-8171-2011
|View full text |Cite
|
Sign up to set email alerts
|

Detection from space of a reduction in anthropogenic emissions of nitrogen oxides during the Chinese economic downturn

Abstract: Abstract. Rapid economic and industrial development in China and relatively weak emission controls have resulted in significant increases in emissions of nitrogen oxides (NO x ) in recent years, with the exception of late 2008 to mid 2009 when the economic downturn led to emission reductions detectable from space. Here vertical column densities (VCDs) of tropospheric NO 2 retrieved from satellite observations by SCIAMACHY, GOME-2 and OMI (both by KNMI and by NASA) are used to evaluate changes in emissions of N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 41 publications
8
117
0
Order By: Relevance
“…That anthropogenic emissions inferred from space are larger than bottom-up inventories for China is consistent with results from many previous studies (Jaeglé et al, 2005;Wang et al, 2007;Zhang et al, 2007;Lin and McElroy, 2011). Our a posteriori budget for anthropogenic emissions over East China is similar to the value of 0.565 TgN for July 2007 estimated by Zhao and Wang (2009).…”
Section: Comparison With Previous Estimatessupporting
confidence: 80%
See 2 more Smart Citations
“…That anthropogenic emissions inferred from space are larger than bottom-up inventories for China is consistent with results from many previous studies (Jaeglé et al, 2005;Wang et al, 2007;Zhang et al, 2007;Lin and McElroy, 2011). Our a posteriori budget for anthropogenic emissions over East China is similar to the value of 0.565 TgN for July 2007 estimated by Zhao and Wang (2009).…”
Section: Comparison With Previous Estimatessupporting
confidence: 80%
“…They are however about half of the inverse estimate by Wang et al (2007) who suggested soil emissions to be more than 40 % of anthropogenic emissions in summer of 1997-2000. In concluding, anthropogenic emissions are found to be the dominant source of NO x over East China for 2006, even in summer when natural sources reach maximum values. The contribution of anthropogenic emissions most likely has increased in more recent years due to their rapid growth (Lin and McElroy, 2011). In the future, the anthropogenic contribution may continue to increase along with the rapid economic and industrial development, if emission control is not taken successfully.…”
Section: Comparison With Recent Bottom-up Estimates For Soil Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term simulations between 2000 and 2010 with relatively high resolution (80 km) were made using a regional-scale, full-chemistry model, the most valuable aspect of this study. Previous studies of emission trends and their variability were conducted with relatively coarse resolution (e.g., Lin and McElroy, 2011;Lamsal et al, 2011). The fine-scale resolution used in the present study will enable comparison among emission inventories.…”
Section: Introductionmentioning
confidence: 97%
“…Satellite NO 2 observations from OMI and other sensors show detectable decreasing trends in NO 2 VCD during the recession (data not shown here). Earlier observations and model simulations [Zhang et al, 2008;Lin and McElroy, 2011;Zhang et al, 2011] have shown that Asian pollution outflow contribute a significant portion of background ozone in western North America. For instance, Zhang et al [2011] estimated that intercontinental pollution (by all emissions outside the United States) and anthropogenic methane enhance background O 3 by 9 ppbv at low-altitude sites and 13 ppbv at high-altitude sites.…”
Section: 1002/2016gl069885mentioning
confidence: 99%